Optimizing Operational Efficiency Through Technological Innovation: A Comparative Analysis Across Industries - Komarudin Komarudin (Politeknik Siber Cerdika Internasional, 2024)
This study examines the role of technological innovation in optimizing operational efficiency across manufacturing, healthcare, logistics, and finance sectors. Using a quantitative approach, data were collected from 200 companies, assessing key operational metrics such as production time, error rates, and cost savings. Findings indicate that manufacturing and logistics sectors experienced the greatest efficiency gains from technologies like automation and the Internet of Things (IoT), with reductions in production time averaging 18% and 15%, respectively. In contrast, the healthcare and finance sectors faced greater regulatory challenges, moderating the immediate impact of technologies like artificial intelligence (AI) and automation. These results align with Rogers’ Diffusion of Innovation Theory, highlighting sectoral variability in technology adoption and efficiency outcomes. The study suggests that phased technology implementation and industry-specific compliance strategies can enhance efficiency gains in regulated sectors. This research provides valuable insights for corporate strategists and policymakers, advocating for tailored approaches to technology adoption to maximize operational benefits. Future studies could explore the impact of innovation on sub-industries within these broader sectors.